Applications of Lasers in Dentistry (International Journal of Food and Nutritional Sciences, 2022)
Background: Since the middle of the 20th century, during the last three and a half decades, lasers have transformed dental care. The ruby laser was created by Theodore Maiman in 1960, and since since, it has become one of the most alluring dental technologies. Initial periodontal treatments, surgery, and implant treatment all make use of lasers. In order for laser to become a tool in the dental arsenal, more study is required. This essay provides information about laser periodontics.